FACTORS AFFECTING STUDENT INTEREST CONTINUING TO HIGHER EDUCATION IN SMA N 11 Sijunjung - -, Afmiko - (Pendidikan Ekonomi, 2014)
In this research study has the purposes one are: 1. Knowing the relationship between the level of intelligence of the students interest to College Continuing Studies in Class XII SMA N 11 Sijunjung, 2. Knowing the relationship between the school environment by Interest Continuing Studies Students to College High School in Class XII N 11 Sijunjung, 3. Knowing the relationship between family environment with Interest Continuing Studies Students to Higher Education in Class XII SMA N 11 Sijunjung. This research is descriptive and associative in collecting the data total sampling conducted at SMAN 11 Sijunjung. Data collection techniques used are documentation and questionnaires. The results of this study indicate that: 1. There is no significant effect relationship between the intelligence of the students desire to continue the study a value of Wald statistic (2.511) < of (67.505) and sig (0.113) > Î± (0.10). 2. There was a significant effect relationship between the school environment with interest to Progress to Higher Education In Class XII SMA N 11 Sijunjung the Wald statistic value (2.933) < of (67.505) and sig (0.087) < Î± (0.10). 3. There is no significant effect on the relationship between family environment with interest to Progress to Higher Education In Class XII SMA N 11 Sijunjung Wald statistic (1.475) < of (67.505) and sig (0.225) > Î± (0.10).